2010
DOI: 10.1002/srin.201000067
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Viscous Behaviour with K2O Additions in the CaOSiO2Al2O3MgOK2O Quinary Slag System

Abstract: The viscosities of CaOSiO220wt%Al2O310 wt%MgO‐K2O quinary slags with CaO/SiO2 from 0.8 to 1.2 at 1773 K with 1–5 wt% K2O additions were measured to estimate the effect of K2O on the viscous behaviour of the slags. The measured viscosity at 1773 K increased with K2O addition at a fixed CaO/SiO2, which is contrary to the effect of Na2O on the viscosity of BF slags. To qualitatively verify the changes in slag structure, FT‐IR spectroscopy was used. It was found that K2O induces Al2O3 to behave as an acidic oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 26 publications
1
51
0
Order By: Relevance
“…It can be observed that viscosities estimated by Nakamoto et al's model decrease monotonously with increasing content of K 2 O for all the three groups. Although both experimental findings [1,2] and the results of our model give a viscosity tendency of first increasing and then decreasing. The position of maximum viscosity is in the field of K 2 O/Al 2 O 3 > 1, whereas it is K 2 O/Al 2 O 3 = 1 for the current model.…”
Section: B the Comparisons Of Measured Viscosity With Those Calculatmentioning
confidence: 46%
See 2 more Smart Citations
“…It can be observed that viscosities estimated by Nakamoto et al's model decrease monotonously with increasing content of K 2 O for all the three groups. Although both experimental findings [1,2] and the results of our model give a viscosity tendency of first increasing and then decreasing. The position of maximum viscosity is in the field of K 2 O/Al 2 O 3 > 1, whereas it is K 2 O/Al 2 O 3 = 1 for the current model.…”
Section: B the Comparisons Of Measured Viscosity With Those Calculatmentioning
confidence: 46%
“…In other words, the viscosity exhibits a maximum with the content of K 2 O, and the position of maximum is in the field of K 2 O/Al 2 O 3 > 1. The phenomenon that the viscosity increases with K 2 O content was also proved by the experimental results of Sukenaga et al [1] and Kim et al [2] However, the viscosity maximums are not found in their work for the high content of Al 2 O 3 .…”
Section: A Effect Of Al 2 O 3 On Viscositymentioning
confidence: 74%
See 1 more Smart Citation
“…Similar phenomena have been observed by other researchers as well. [9][10][11] Recently, Zhang and Chou 11) examined the effects of K2O addition on the viscosity of CaOSiO2-Al2O3 melt for Al2O3 content of 2-10 mol%. They found viscosity of the 38.2CaO-59.8SiO2-2.0Al2O3 (mol%) melt increased with the K2O additon when K2O content was less than 3 mol%, but decreased with K2O content when K2O content > 3 mol%.…”
Section: Introductionmentioning
confidence: 99%
“…15,16) Thus, the change of slag structure with K 2 O seems to be determined by the dual balance of the following conditions: ① the modification of complex silicate structures to simpler dimers and monomers of [Si 2 O 7 ] 6 − , 5 − due to the ionic charge-compensating effect. According to a series of literatures [17][18][19] it is likely that the abovementioned effect of K 2 O on the aluminate structure is more dominant. Furthermore, according to Sohn I, 4) after treated by K 2 O, the Si-O-Al bonding within the slag increased, thus polymerizing the slag to form complex aluminates and aluminosilicate structures.…”
Section: Influence Of Alkali Oxidesmentioning
confidence: 99%